Smart Technology Based Modernization to Maximize the Potential of Fried Shallot MSMEs - Aslindar, Dwi Astarani; Hidayah, Asmi Ayuning; Syamara, Ameliyana Rizky (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in Indonesia’s economy, particularly in the high-value fried shallot agro-industry. However, many MSMEs, such as Piknik Food, encounter persistent challenges in production and management due to manual practices, leading to limited capacity (15 packs/day), inconsistent product quality, and restricted market reach. This community engagement program employed a participatory-collaborative approach through stages: socialization, training, technology adoption, mentoring, and sustainability. Interventions emphasized smart technology-based modernization, including the application of production machinery (peeler, spinner, continuous sealer), financial digitalization, and the implementation of digital marketing strategies via social media and e-commerce platforms. The results indicated a 90% increase in production capacity (28–30 packs/day), a 32–35% reduction in oil content approaching SNI standards, improved hygienic packaging, and approximately 20% market expansion. These findings underscore that smart technology-based modernization enhances productivity, product quality, and competitiveness while supporting the achievement of the Sustainable Development Goals.